Strategies for Computer-aided Drug Design in Developing Inhibitors for Dengue Virus (Flavivirus Genus) - Patidar, Ravina (International Journal of Pharmaceutical & Biological Archive, 2025)
This study explores strategic applications of computer-aided drug design (CADD) to develop potential inhibitors against dengue virus (DENV) (Flavivirus genus), focusing on the molecular docking evaluation of gossypol and four of its derivatives: Schiff base, acetylated, dimethoxy, and hydrazone. Using AutoDock Vina, nine docking poses were generated for each ligand, with Mode 1 identified as the most stable configuration across all compounds. Parent gossypol exhibited the strongest binding affinity (–9.3 kcal/mol), facilitated by extensive hydrogen bonding and hydrophobic interactions within the viral target’s active site. Gossypol hydrazone followed closely, benefiting from polar hydrazone functionalities that enhanced receptor engagement (–7.2 kcal/mol). Dimethoxy gossypol displayed moderate affinity due to hydrophobic enhancements, whereas Schiff base and acetylated gossypol showed diminished binding, likely due to steric hindrance and reduced polar contacts. Root mean square deviation analyses affirmed the stable binding of gossypol derivatives and the adaptability of the receptor’s pharmacophore region. The findings demonstrate that small functional group modifications significantly influence binding strength and orientation. Hydrazone substitution emerged as a promising strategy, whereas excessive steric bulk, as in acetylation, adversely affected binding. These results underscore the importance of polarity, scaffold rigidity, and hydrophobic balance in designing potent inhibitors. The study advocates further refinement of the gossypol scaffold, incorporating dynamic simulation and structure-activity relationship analysis to optimize antiviral lead compounds. The integration of docking simulations into early-stage drug discovery proves valuable for rational inhibitor design against DENV.